2018
DOI: 10.1021/acs.jpcc.8b03306
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Electrodeposition of the Hierarchical Cobalt Oxide Nanostructure from Spent Lithium-Ion Batteries: Its Application as a Supercapacitor Electrode

Abstract: In this study, electrodeposition of cobalt oxide (Co 3 O 4 ) from spent lithium-ion batteries is successfully enhanced by the magnetic field effect. In the presence of magnetic field, well-defined hierarchical Co 3 O 4 nanostructures with higher electroactive surface area are formed during the electrodeposition process. Electrochemical analysis shows that the enhanced Co 3 O 4 nanostructures exhibit excellent charge storage capabilities of 1273 F g −1 at 1 A g −1 , approximately 4 times higher than the electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 46 publications
1
33
0
Order By: Relevance
“…S1b. It can be seen that all of the NiCo 2 S 4 -coated Ni mesh samples were uniformly covered with different types of nanostructure, including petal-shaped structures similar to the top view of a rose, spherical nanoparticles, and interconnected nanoflakes 3537 . We clearly observed that the nanostructure, depth, thickness, and length of the vertical interconnected nanoflakes were affected by the ratio of Ni to Co.…”
Section: Resultsmentioning
confidence: 99%
“…S1b. It can be seen that all of the NiCo 2 S 4 -coated Ni mesh samples were uniformly covered with different types of nanostructure, including petal-shaped structures similar to the top view of a rose, spherical nanoparticles, and interconnected nanoflakes 3537 . We clearly observed that the nanostructure, depth, thickness, and length of the vertical interconnected nanoflakes were affected by the ratio of Ni to Co.…”
Section: Resultsmentioning
confidence: 99%
“…However, the electrochemical performance of the first developed ZHC is pretty moderate in this initial stage with only 300 cycles and 70 % capacitance retention. According to the Trasatti's analysis, the charge storage mechanisms of electrodes can be divided into three categories: the slow faradaic contribution which is limited by solid‐state ion diffusion, the fast faradaic contribution (also known as pseudocapacitance) from the quick charge‐transfer process at surfaces, and the non‐faradaic contribution from the electric double layer effect [18,25,26,29] . The former one can be regarded as diffusive or battery‐type charge storage while the latter two are known as capacitive charge storage.…”
Section: The Mechanism Of Zhcsmentioning
confidence: 99%
“…Aboelazm et al . reported on the recovery of cobalt oxide (Co 3 O 4 ) from spent Li‐ion battery and tested its performance as a supercapacitor material in 3‐electrode cell . Although the recovered Co 3 O 4 showed a specific capacitance of 1273 F g −1 , the recovery process suffers from the high cost due to the multi‐steps used to selectively deposit Co 3 O 4 under magnetic field .…”
Section: Introductionmentioning
confidence: 99%
“…Aboelazm et al reported on the recovery of cobalt oxide (Co 3 O 4 ) from spent Li-ion battery and tested its performance as a supercapacitor material in 3-electrode cell. [18] Although the recovered Co 3 O 4 showed a specific capacitance of 1273 F g À 1 , the recovery process suffers from the high cost due to the multi-steps used to selectively deposit Co 3 O 4 under magnetic field. [18] Rochaab et al were able to recover CuFe 2 O 4 ferrites from spent Li-ion battery, which showed a specific capacitance of 2.4 F g À 1 with high charge efficiency and reversibility upon use in supercapacitor cell.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation